Evaluation of bioactivities and formulation of face mask from Sargassum sp. extract - Hong, Dang Diem; Vy, Phan Bao; Hoai Thu, Ngo Thi; Khoi, Tran Xuan; Ha, Nguyen Cam; Tam, Luu Thi (Academia Journal of Biology, 2018)
Brown seaweeds, particularly Sargassum genus, contain large amount of polysaccharides, such as alginate and fucoidan, which are widely applied to related health care approaches. Obviously, this genus is a potential alternative resource for cosmetic industry with its extract gained a great deal of biochemical composition and bioactivity. This study showed that the protein, lipid, total carbohydrate, chlorophyll and carotenoid contents of Sargassum sp. which collected in Khanh Hoa, Vietnam were 10.45 ± 1.15%, 1.90 ± 0.12%, 50.55 ± 1.05%, 0.25 ± 0.03 mg/g and 0.104 ± 0.001 mg/g of dry weight (DW), respectively. The hot water extract of Sargassum sp. showed high free radical scavenging activity (85.82 ± 1.89% at 50 mg/mL), antibacterial activity with the range of minimal inhibitory concentrations (MIC) from 25–100 mg/mL and tyrosinase inhibitory activity (16.19 ± 1.05%, 22.94 ± 1.23%, 104.16 ± 4.15% at concentrations of 50, 100 and 200 mg/mL). The formula of face mask from 10% of Sargassum sp. extract gained antioxidant and tyrosinase inhibitory activity with 61.67 ± 0.06% and 29.064 ± 0.06%, respectively. This product was also evaluated for the physical properties included organoleptic (brown color with specific odor), pH, homogeneity, spread ability and irritation test. The bacterial criteria, heavy metal levels of face mask were also recognized to evaluate for safety of human health following Ministry of Health standard.